A class of rigid linker-bearing glucosides for membrane protein structural study. Issue 3 (16th December 2015) - Sadaf, Aiman; Mortensen, Jonas S.; Capaldi, Stefano; Tikhonova, Elena; Hariharan, Parameswaran; Ribeiro, Orquidea; Loland, Claus J.; Guan, Lan; Byrne, Bernadette; Chae, Pil Seok
Abstract : Novel glycoside amphiphile (NDT-C11) displays favorable behavior in maintaining both protein stability and conformational flexibility compared to DDM and MNG-3. Abstract : Membrane proteins are amphipathic bio-macromolecules incompatible with the polar environments of aqueous media. Conventional detergents encapsulate the hydrophobic surfaces of membrane proteins allowing them to exist in aqueous solution. Membrane proteins stabilized by detergent micelles are used for structural and functional analysis. Despite the availability of a large number of detergents, only a few agents are sufficiently effective at maintaining the integrity of membrane proteins to allow successful crystallization. In the present study, we describe a novel class of synthetic amphiphiles with a branched tail group and a triglucoside head group. These head and tail groups were connected via an amide or ether linkage by using a tris(hydroxylmethyl)aminomethane (TRIS) or neopentyl glycol (NPG) linker to produce TRIS-derived triglucosides (TDTs) and NPG-derived triglucosides (NDTs), respectively. Members of this class conferred enhanced stability on target membrane proteins compared to conventional detergents. Because of straightforward synthesis of the novel agents and their favourable effects on a range of membrane proteins, these agents should be of wide applicability to membrane protein science.